Intubation Success through I-Gel® and Intubating Laryngeal Mask Airway® Using Flexible Silicone Tubes: A Randomised Noninferiority Trial - Latha Naik; Neerja Bhardwaj; Indu Mohini Sen; Rakesh V. Sondekoppam (Anesthesiology Research and Practice)
Introduction. The study aims to test whether flexible silicone tubes (FST) improve performance and provide similar intubation success through I-Gel as compared to ILMA. Our trial is registered in CTRI and the registration number is “CTRI/2016/06/006997.” Methods. One hundred and twenty ASA status I-II patients scheduled for elective surgical procedures needing tracheal intubation were randomised to endotracheal intubation using FST through either I-Gel or ILMA. In the ILMA group (n=60), intubation was attempted through ILMA using FST and, in the I-Gel group (n=60), FST was inserted through I-Gel airway. Results. Successful intubation was achieved in 36.67% (95% CI 24.48%–48.86%) on first attempt through I-Gel (n=22/60) compared to 68.33% (95% CI 56.56%–80.1%) in ILMA (n=41/60) (p=0.001). The overall intubation success rate was also lower with I-Gel group [58.3% (95% CI 45.82%–70.78%); n=35] compared to ILMA [90% (95% CI 82.41%–97.59%); n=54] (p<0.001). The number of attempts, ease of intubation, and time to intubation were longer with I-Gel compared to ILMA. There were no differences in the other secondary outcomes. Conclusion. The first pass success rate and overall success of FST through an I-Gel airway were inferior to those of ILMA.